Pengaruh Strategi Pemasaran 4P (Product, Place, Price, Promotion) Dan Literasi Digital Pada Momoyo Plosokandang Terhadap Minat Beli Konsumen Di Wilayah Tulungagung - Therina Wandira; Kadeni Kadeni; Sulastri Rini Rindrayani (Science and Education Journal (SICEDU), 2026)
This study aims to analyze the influence of Product, Price, Place, Promotion, and Digital Literacy on Consumer Purchase Intention at Momoyo Plosokandang in Tulungagung. This research employed a quantitative approach with 287 respondents selected through purposive sampling. Data were analyzed using the SEM-PLS method with SmartPLS 3 software. The results indicate that Product, Price, Promotion, and Digital Literacy have a positive and significant effect on Consumer Purchase Intention, while Place has no significant effect on Consumer Purchase Intention. The R-Square value of 0.532 indicates that Product, Price, Place, Promotion, and Digital Literacy explain 53.2% of the variance in Consumer Purchase Intention, while the remaining 46.8% is explained by other factors outside the study. The simultaneous test shows that Fcount (63.87) is greater than Ftable (2.25), indicating that all independent variables simultaneously have a significant effect on Consumer Purchase Intention. The study concludes that improving product quality, implementing appropriate pricing strategies, conducting effective promotions, and enhancing consumers’ digital literacy can increase consumer purchase intention at Momoyo Plosokandang.